2017
DOI: 10.1038/s41598-017-16044-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac arrest patients’ temperature management after the publication of 2015 AHA guidelines for resuscitation in China

Abstract: A survey was performed to assess the current management of targeted temperature management (TTM) in patients following cardiac arrest (CA) and whether healthcare providers will change target temperature after publication of 2015 American Heart Association guidelines for resuscitation in China. 52 hospitals were selected from whole of China between August to November 2016. All healthcare providers in EMs and/or ICUs of selected hospitals participated in the study. 1952 respondents fulfilled the survey (86.8%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Finally, there is an alternative explanation for the current results is clinician bias in selecting the TTM strategy. Several studies have reported that treating physicians are more likely to select TTM at 33°C for patients they believe to have more severe hypoxic insults in order to maximize the protective effects of TTM against brain damage [1,30]. If a clinical judgment was made based on patient severity, the allocation of more severe patients to the TTM group at 33°C would bias our results to favor 36NTFD.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, there is an alternative explanation for the current results is clinician bias in selecting the TTM strategy. Several studies have reported that treating physicians are more likely to select TTM at 33°C for patients they believe to have more severe hypoxic insults in order to maximize the protective effects of TTM against brain damage [1,30]. If a clinical judgment was made based on patient severity, the allocation of more severe patients to the TTM group at 33°C would bias our results to favor 36NTFD.…”
Section: Discussionmentioning
confidence: 96%
“…The number of AEDs per 100,000 residents was lower than that in many developed countries (17.5, 13, and 5 in the developed Chinese cities of Shenzhen, Haikou, and Shanghai, respectively) [ 9 ]. Target temperature management for cardiac arrest patients was still in the early stage, and only 7.8% of physicians and 5.7% of nurses had implemented therapeutic hypothermia for cardiac arrest patients [ 10 ]. Nevertheless, Chinese emergency physicians have been working hard to improve the prognosis of cardiac arrest patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent guidelines have recommended targeted temperature management (TTM) as the neuroprotective intervention in resuscitation care of CA [3,5,6]. Refractory shock inducing recurrent CA or multiorgan failure (MOF) typically results in deaths within the rst 24 hours after return of spontaneous circulation (ROSC), while neurological injury causes later deaths after CA [7].…”
Section: Introductionmentioning
confidence: 99%